SOCIO-PSYCHOLOGICAL PREDICTORS FORMING SMOKING CESSATION INTENTIONS - Hakobjanyan, A. R. (Modern Psychology, 2020)
This article presents an analysis of data from a study of smoking cessation as a health behavior. The process of quitting smoking can be difficult expressed in different ways. Since health is a systemic phenomenon, reflected in physical, mental and social well-being, the steps and actions to maintain it must be considered systematically. We believe that quitting smoking will contribute to the development of a generally healthy lifestyle, as the processes at the physiological and psychological levels will change. In particular, the purpose of this article is to present the predictors underlying the intention to smoking cessation and their possible role in the development of the desired behavior. The research was conducted on the methodological basis of the theory of planned behavior. A sample of 70 smokers was included in the study sample. Regression analysis was conducted of the research data. According to the analysis, both the attitudes about the possibility of changing the behavior and the autonomous motivational regulation play an important role in the intention to implement the behavior.
Keywords: smoking cessation; intention; psychological attitudes; , attitudes; autonomous motivation; health behaviour; Theory of Planned Behaviour